2012
DOI: 10.1080/15323269.2012.666647
|View full text |Cite
|
Sign up to set email alerts
|

Access to and Dissemination of Health Information in Africa: The Patient and the Public

Abstract: African countries are faced with a number of daunting health challenges. These include maternal mortality, child and infant mortality, malaria, human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS), cholera, and so on. At such a time, Africans need access to health information. Unfortunately, access to and dissemination of health information in Africa is still at its lowest ebb. This article, therefore, examines the benefits of access to health information and the different methods adopted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…family, friends, and informal community groups) [3]. This approach is preferred for the transmit of information and teaching of skills to encourage desired behavior changes [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…family, friends, and informal community groups) [3]. This approach is preferred for the transmit of information and teaching of skills to encourage desired behavior changes [5].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, communities may use their own traditional approaches to message delivery, including songs, drama, storytelling, role-play, proverbs, community meetings and poems. Previous studies have shown that traditional modes of communication and knowledge transfer are preferable for poor and rural populations since they usually do not require advanced technology, they are typically very interesting and emotive, and they are easily understood and accepted by the community [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…It is used for a variety of reasons, including self-education prior to consultation with a health professional, verifying and adding to information obtained from health professionals and adding to women's overall health knowledge. Anasi (2012) concludes that the capabilities of ICTs in bridging the digital gap and resolving the health information conundrum in Africa are not in doubt.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Information is an essential factor to develop patient's knowledge and empowers them in their decision-making. 14 Respondents were sampled ensuring representativeness with regards to, sex, age, social class, and region. They were contacted using random digit dialling, ensuring that those who had listed and unlisted telephone numbers had equal probability of being contacted as well as those using both mobile and landline numbers.…”
Section: The Royal College Of Obstetricians and Gynaecologist (Rcog)mentioning
confidence: 99%
“…Nonetheless, whatever the choice for parents in any country following an antenatal diagnosis of FFA, the need for the decision to be an informed one is paramount. Information is an essential factor to develop patient's knowledge and empowers them in their decision‐making . Acknowledging all maternity patients' popularity with accessing information from relatives and friends, it is important to assess what the general public's knowledge is on FFA, PPC, and TOP as this will potentially show how accurate this information sharing is.…”
Section: Introductionmentioning
confidence: 99%